2015
DOI: 10.1371/journal.pone.0133643
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Let-7a Is Associated with Chemoresistance in Primary Breast Cancer

Abstract: Chemotherapy resistance remains an important problem in the breast cancer clinic. The ability to predict the patients who would respond to a distinct therapy would help to optimize tailored treatment options. miRNAs can mediate a number of genes in response to drug-induced acute cellular stress. Several studies suggest that let-7 miRNA may be involved in the chemosensitivity of cancer cell lines in vitro. However, it is not known whether this phenomenon occurs in clinical breast tumors. The present study showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 16 publications
(19 reference statements)
2
31
0
Order By: Relevance
“…Alterations of this miRNA in our study were similar to those described in the literature earlier by our group as well as by other investigators [22,23,4042]. The aberrant expression of let-7a in many types of human cancers including PC indicates its tumor suppressor role [22,24,43,44]. For example, over-expression of let-7a with diflourinated-curcumin (CDF) mediated tumor regression with reduced EZH2, Notch-1, and EpCAM expression in PC in our previous study [22].…”
Section: Discussionsupporting
confidence: 90%
“…Alterations of this miRNA in our study were similar to those described in the literature earlier by our group as well as by other investigators [22,23,4042]. The aberrant expression of let-7a in many types of human cancers including PC indicates its tumor suppressor role [22,24,43,44]. For example, over-expression of let-7a with diflourinated-curcumin (CDF) mediated tumor regression with reduced EZH2, Notch-1, and EpCAM expression in PC in our previous study [22].…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, emerging evidence has demonstrated that members of the let-7 family of miRNAs are downregulated in a number of types of human cancer, and that low let-7 expression has been correlated with resistance to chemotherapeutics (37,38). Downregulation of let-7 was also associated with chemoresistance in breast cancer cells (39). In addition, Sugimura et al (38) reported that low expression of let-7b and let-7c was significantly associated with a poor response to chemotherapy in esophageal squamous cell carcinoma, and that transfection of let-7c restored sensitivity to cisplatin and increased the rate of apoptosis following exposure to cisplatin in vitro assays.…”
Section: Discussionmentioning
confidence: 99%
“…Let-7a, a member of microRNA let-7 family, has been linked to various cancer types, e.g., breast cancer, non small cell lung cancer (NSCLC), pancreatic cancer, colon cancer [19-22]. It has been reported that overexpression of let-7a could sensitize resistant breast cancer cells to epirubicin in vitro [22].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that overexpression of let-7a could sensitize resistant breast cancer cells to epirubicin in vitro [22]. In some studies, let-7a has been shown to inversely correlate with well-known oncogenes, including HMGA2[23], and positively regulate classical apoptosis-related gene CASP3[24].…”
Section: Introductionmentioning
confidence: 99%